2013
DOI: 10.3758/s13428-013-0352-z
|View full text |Cite
|
Sign up to set email alerts
|

The development and analysis of tutorial dialogues in AutoTutor Lite

Abstract: The goal of Intelligent Tutoring Systems (ITS) that interact in natural language is to emulate the benefits a well-trained human tutor provides to students, by interpreting student answers and appropriately responding to encourage elaboration. BRCA Gist is an ITS developed using AutoTutor Lite, a web-based version of AutoTutor. Fuzzy-Trace Theory theoretically motivated the development of BRCA Gist, which engages people in tutorial dialogues to teach them about genetic breast cancer risk. We describe an empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 43 publications
0
31
1
1
Order By: Relevance
“…This represents a substantial improvement over the 85% of responses judged to be appropriate in the first iteration of BRCA Gist reported by Wolfe, Widmer, and colleagues (2013) who also found that the percentage of appropriate responses correlated with learning outcomes. Perhaps because, in the current study, BRCA Gist performance approaches ceiling, the percentage of appropriate responses did not predict performance on the assessment instruments, Fs<1.…”
Section: 1 Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This represents a substantial improvement over the 85% of responses judged to be appropriate in the first iteration of BRCA Gist reported by Wolfe, Widmer, and colleagues (2013) who also found that the percentage of appropriate responses correlated with learning outcomes. Perhaps because, in the current study, BRCA Gist performance approaches ceiling, the percentage of appropriate responses did not predict performance on the assessment instruments, Fs<1.…”
Section: 1 Resultsmentioning
confidence: 60%
“…Thus, if the tutor is appropriately interpreting verbal inputs from the users, an answer given a high CO score as a measure of semantic similarity should contain more relevant content, as measured by the researcher applying a rubric, than in an answer given a lower CO score. Applying a conditional reliability procedure (Wolfe, Widmer et al, 2013) the two judges achieved .89 agreement with a range of .84 with responses to the question “what should someone do if she receives a negative result for genetic risk of breast cancer,” to .94 for responses to the question "how does breast cancer grow and spread." To assess the effect of the dialogues on learning, we correlated coverage scores with scores on the 52-item multiple-choice test assessing declarative knowledge of genetic risk of breast cancer, gist comprehension scores, and risk assessment percent correct.…”
Section: 1 Methodsmentioning
confidence: 99%
“…An ITS is a computer-based system using artificial intelligence techniques to mimic one-on-one human “tutoring.” 19 Individual human tutoring is arguably the “gold standard” for facilitating deep conceptual understanding, 20,21 and there is evidence that the best ITS's produce gains comparable to human tutors. 22 An ITS is not the same as decision aids such as Gail, Claus, or BRCAPRO.…”
Section: The Brca Gist Intelligent Tutoring Systemmentioning
confidence: 99%
“…ITSs in medicine are rare, 28 and although computer-tailored interventions have demonstrable benefits in areas such as mammography screening, 29 BRCA Gist appears to be the first ITS applied to lay people's medical decision making. 19 …”
Section: The Brca Gist Intelligent Tutoring Systemmentioning
confidence: 99%
“…The content for BRCA-Gist was authored by researchers at Miami University, making it one of the first AutoTutor descendants authored outside of Memphis. A recent study using BCRA-Gist reported that the AutoTutor Lite's evaluations of student contributions predicted student outcomes on a posttest (Wolfe et al 2013). A second study indicated that AutoTutor Lite outperformed a static web-based tutorial for reducing internal inconsistency (e.g., negating prior assumptions) but did not improve quantitative estimates of risk probabilities (Wolfe et al 2012).…”
Section: Delivery Technologies and Architecturesmentioning
confidence: 99%